(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
Extrusion technology is emerging as a preferred method in agro-food processing, leveraging mixing, forming, texturing, and cooking to develop innovative food products. Extrusion cooking is a high-temperature, short time process that effectively inactivates enzymes and minimizes microbial contamination. The preference for extrusion cooking stems from its ability to achieve high productivity while preserving nutrients more effectively than conventional cooking techniques. The food processing sector has come to rely on extrusion technology due to its numerous benefits, which surpass those of other processing techniques. As a cost-effective approach, it provides a flexible platform for processing various food products from different groups, enabling adjustment to ingredients and processing parameters. Extrusion technology is employed in the food processing industry for the manufacture of various food products, such as snacks, pasta, breakfast cereals, pet foods, supplementary foods, and textured foods. It is an economically viable method for recovering and reutilizing food processing by-products and residues, thereby reducing waste and enhancing food security. The adaptability of extrusion technology facilitates the development of nutritionally enhanced products and value-added products through the strategic combination of cost-effective raw materials. Extruded products exhibit reduced moisture content, extended shelf-life, and enhanced microbiological safety. This technology offers several advantages, including product versatility, superior quality, enhanced productivity, and minimized processing time.